Implementation of Child Character Education in the Mother School Program in Magelang Tengah District, Magelang City: Implementasi Pendidikan Karakter Anak pada Kegiatan Sekolah Ibu di Kecamatan Magelang Tengah Kota Magelang - Nurhayati, Nely; Oktradiksa, Ahwy (Prosiding University Research Colloquium, 2024)
Implementation of character education for children through the Mother School Program in Central Magelang District, Magelang City is an activity plan that involves the role of Pregnant Women and Mothers who have children under 5 years of age to provide scientific knowledge about the importance of children’s character education from the First 1000 Days of Life and activities This is also a form of community service in reducing the number of stunted children in Magelang City, especially in Central Magelang District. The main aim of this research is to identify the strategies and methods used in transmitting children’s character values from an early age. This research uses a qualitative approach with observation and interview methods as data collection techniques. The research results show that the Mother School Program consistently integrates character values such as honesty, justice, respect and empathy. Facilitators play an important role in providing direct examples and guiding program participants in building good character.